Solid surface materials based on reaction mixtures with two blowing agents
Patent Information
- Application Number
- JP2025521154
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-11-23
- Filing Date
- 2023-10-06
- Publication Date
- 2026-10-14
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to the preparation of polyurethane-based structurally integrated skin solid surface materials. The present invention provides a reaction mixture containing a polyol, a polyisocyanate, and at least two different types of blowing agents with different behaviors. The present invention also relates to a method for producing the solid surface material from the reaction mixture. [Background technology]
[0002] A recent publication calls for the invention of a new solid surface made of foamed polyurethane based on aliphatic isocyanates, which has high light resistance and excellent mechanical properties. Unlike other solid surfaces on the market, this solid surface has a one-piece sandwich structure with a foam core and a dense skin. This structure provides better mechanical properties at a lower weight. To ensure the material is durable and allows for multiple repairs by sanding, the skin must be significantly thicker than in conventional one-piece PU pieces that are not designed to withstand damage.
[0003] Here, we propose an efficient and reliable solution to this problem by providing an innovation that makes it possible to obtain a much thicker and more uniform skin than that offered by commercially available polyurethane pieces. This skin is hard, thick, and uniform under the various working conditions that can occur in an industrial environment.
[0004] Solid surface materials are defined as materials or molded articles formed by a polymer matrix, pigments, and fillers that can be processed by sheet molding. They are also defined in ISO standard 19712-1 UNE.EN:2013. Solid surface materials are homogeneous products, i.e., they have the same composition throughout their thickness. This characteristic allows them to be easily repaired by simple sanding.
[0005] Typically, solid surface materials are used in bathroom and kitchen fixtures such as sinks, toilets, or countertops. Currently available solid surface materials contain a polymer matrix made from acrylic or polyester resins. The most frequently used filler is alumina trihydrate.
[0006] Structurally integrated skin materials are defined by an isotropic chemical composition, but have a large density difference between the center (core) and the surface (skin) of the material. Typical concentrations for these materials are in the range of 1100-1400 kg / m for the skin. 3 , 800 to 400 kg / m in the core 3 is.
[0007] Solid surface materials are characterized by a thick skin that allows for repeated sanding without damaging the surface, for example, to repair a damaged surface.
[0008] Apart from casting a solid surface material to give it its final shape, another common route is to fabricate a slab followed by a post-fabrication process such as thermoforming. This means that the final shape of the solid surface material is achieved after the resin has fully cured. Thus, traditional solid surface materials are based on thermoplastic resins. Thermoforming, cutting, and gluing are often used to create complex shapes that cannot be made by direct casting, but they have the disadvantage of being time-intensive manual processes.
[0009] Conventional solid surface products are often sensitive to UV radiation and acids, bases, and cleaning agents. As a result, they cannot be used in outdoor applications without additional radiation protection. Furthermore, typical cleaning agents, such as isopropanol, are known to lead to stress corrosion cracking. Furthermore, it is desirable to manufacture solid surface materials by reaction injection molding (RIM) because it is a fast and efficient process. However, the polymer matrices mentioned above are not well suited to this manufacturing method because they require long curing times of up to two hours. Furthermore, conventional matrices exhibit high volumetric shrinkage during the curing process, which adversely affects dimensional stability, especially in common low-pressure RIM or casting processes. Therefore, it is desirable to use a system that is (i) UV-resistant without additional processing, (ii) has good dimensional stability during the curing process, and (iii) has a short curing time and can be processed by RIM.
[0010] Polyurethane-based solid surface materials are described in EP 3354669 and WO 2018 / 172413. The preferred method for producing these materials is reaction injection molding (RIM). However, volume shrinkage during curing is problematic when using this process, resulting in pores, cavities, and deviations from the desired shape of the final product. EP 3354669 proposes the combination of an irreversible blowing agent and a reversible blowing agent to produce such materials. However, as the research underlying this invention has shown, simply combining an irreversible blowing agent and a reversible blowing agent in any proportion is not sufficient to produce such materials. This application is the first to describe the ingredients and reaction conditions necessary to actually produce a material with the properties described in EP 3354669. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] European Patent No. 3354669 [Patent Document 2] International Publication No. 2018 / 172413 Brochure Summary of the Invention [Problem to be solved by the invention]
[0012] The problem underlying the present invention can therefore be defined as providing a solid surface material having a sandwich structure with a thick integral skin and a foam core. [Means for solving the problem]
[0013] This problem is solved by the embodiments defined by the claims and the following description. Thus, in a first embodiment, the present invention provides: (i) thickness of 8 mm to 50 mm; (ii) 0.9 g / cm within 1.5 mm below the surface 3 ~1.4g / cm 3 The average density of, and (iii) 0.25 g / cm in the polymer at least 2.5 mm below the surface 3 ~0.8g / cm 3 Average density of A polyurethane part having at least one region characterized by: a) Polyol component A1; b) a polyisocyanate component A2 containing at least 60% by weight of aliphatic and cycloaliphatic polyisocyanates; c) at least one reversible foaming agent B1; d) at least one irreversible blowing agent B2, and e) at least one catalyst C The present invention relates to a polymerizable composition comprising:
[0014] In a preferred embodiment, the composition further comprises at least one additive selected from the group consisting of pigments, flame retardants, dispersants, emulsifiers, cell regulators, foam stabilizers, biocides and inorganic fillers.
[0015] The "polyurethane part" is the product resulting from the reaction of compounds A1 and A2 contained in the polymerizable composition. In a preferred embodiment of the present invention, the polyurethane part has a thickness of 8 mm to 50 mm, more preferably 8 mm to 40 mm, and most preferably 10 mm to 30 mm.
[0016] Preferably, the area characterized by the thickness and density defined above is at least 20 mm, more preferably at least 50 mm, in each of the other two dimensions. This does not exclude that other portions of the polyurethane part may be thicker or thinner and / or have a density different from the limits given in this application. For the most efficient use of material, it is particularly preferred that the part have the thickness defined above over at least 50% or more, more preferably at least 75% of its total area.
[0017] Preferably, the polyurethane part has at least two parallel surfaces. However, it can have any other shape suitable for the intended purpose of the polyurethane part. The polyurethane part is preferably a product selected from the group consisting of bathroom parts, kitchen equipment, shells for electrical and electronic devices, cases for electrical equipment, vehicle parts, building parts, indoor furniture, and outdoor furniture.
[0018] Preferred bathroom components are selected from the group consisting of bathtubs, sinks, toilets, toilet seats, bath panels and shower trays.
[0019] Preferred pieces of kitchen equipment are selected from the group consisting of kitchen sinks, cookers, heated display cabinets, countertops and ovens.
[0020] Preferred building components are selected from the group consisting of door panels, wall panels, fence panels, skylights, wall panels, door frames and window frames.
[0021] Preferred electrical appliance cases are selected from the group consisting of automated teller machine, refrigerator, and washing machine cases.
[0022] Preferred vehicle parts are selected from the group consisting of automobile, airplane, train and watercraft parts.
[0023] Preferred interior furniture pieces are selected from the group consisting of shelves, beds, chairs, desktops, and tables.
[0024] A preferred outdoor furniture component is a patio furniture component.
[0025] Due to the combined action of the blowing agents, the polyurethane part has a higher density near the surface and a lower density in its core due to the stronger foaming. Thus, in a preferred embodiment of the invention, the material has a density of 1.1 g / cm within 1.5 mm below the surface. 3 to 1.4 g / cm 3 The average density of the cellulose acylate is
[0026] From the description of the manufacturing process below, it is clear that the density of the material follows a decreasing gradient, starting with the highest density at the surface and ending with the lowest density at the center. Therefore, the density within the two zones defined above is not uniform. However, the average density of the core can be easily determined by cutting a piece of material located at least 2.5 mm below the surface and determining its density.
[0027] Similarly, the density of the surface layer can be readily determined by cutting out a piece of material containing the skin and core regions, measuring the thickness of the skin and core, and subtracting the weight of the core, the density of which has been determined as described above, from the total weight of the cut piece. Because the density of the material is highest directly at the skin and then gradually decreases over the first few millimeters below the skin, the density of the skin determined above is necessarily an average value.
[0028] A "polymerizable composition" as referred to in this application is a composition comprising the components defined above in a form capable of initiating a reaction, said reaction causing crosslinking of the polyol and the polyisocyanate to yield a polyurethane polymer. Thus, at least components A1 and A2 are present as a homogeneous mixture.
[0029] Reversible Foaming Agent B1 A "reversible" blowing agent is a compound that changes from a liquid phase to a gas phase when exposed to a determined temperature and pressure, but returns to the liquid phase when the pressure is increased or the temperature is decreased. Preferably, the reversible blowing agent should be a liquid at atmospheric pressure and room temperature.
[0030] The reversible blowing agent B1 is a liquid having a boiling point at atmospheric pressure of preferably 5°C to 50°C, more preferably 10°C to 30°C, and most preferably 10°C to 20°C.
[0031] In a preferred embodiment, the reversible blowing agent B1 has a vapor pressure at 50°C of 100 kPa to 300 kPa.
[0032] The above-defined properties of the first blowing agent are important for obtaining a foamed material with a dense surface. Blowing agents with these properties evaporate in the center of the polymerizable composition as the reaction begins and generates heat. However, above a certain combination of pressure and temperature, they remain liquid or return to their original liquid state. This occurs near the surface, where they are cooled by the surrounding environment. Thus, a lower-density foamed structure develops in the core, while a solid, integrated skin with a higher density develops near the surface.
[0033] Preferred reversible blowing agents B1 are organic molecules of less than 8 carbon atoms having a boiling point at atmospheric pressure of 10°C to 50°C.
[0034] Products that can be used as reversible foaming agents for the production of solid surface materials are subdivided into three families: 1. Non-halogenated organic compounds: These are always molecules containing carbon and hydrogen. They are interesting because they are easily available on the market and inexpensive. However, their high flammability / explosiveness requires treatment in ATEX equipment and / or a controlled atmosphere. These compounds are preferably the following: 1a. Partially oxidized hydrocarbons: This contains carbon, hydrogen atoms and at least one oxygen atom in its molecular composition. These products are esters, ethers, ketones, aldehydes and formic acid. Alcohols must be excluded from this group because of their reactivity with isocyanates. 1b. Alkanes and cycloalkanes: These contain only carbon and hydrogen atoms of the formula H B C A (where 1 < A < 8 and B = 2A or B = 2×A + 2). They are dangerous because of their high flammability, but are soluble in component A and not reactive. Preferred compounds of this family are butane, isopentane and cyclopentane.
[0035] 2. Halogenated organic compounds: This has the general formula C A H B X J (where 0 < A < 6, H + X = 2×A + 2 and X is F, Cl or Br). They have been used because of their low flammability. What are the subfamilies of this second group? 2a. CHC chlorinated organic compounds: These compounds have the general formula C A H B Cl J (where 0 < A < 6 and B + J = 2xA + 2). Methylene chloride CH2Cl2 is preferred. 2b. CFCs: Compounds containing chlorine, fluorine and carbon, such as the so-called CFC-11 (CFCl3 trichlorofluoromethane). The general formula is C A F J Cl k (where 0 < A < 6 and J + K = 2xA + 2). 2c. HCFCs: Compounds containing chlorine, fluorine, hydrogen, and carbon: These are represented by the general formula H B C A F J Cl k (where 0 < A < 6 and B + J + K = 2xA + 2). The so-called HCFC-22 (HCF2Cl chlorodifluoromethane), which has low toxicity, is preferred. 2d. HFC (Compounds containing fluorine, hydrogen, and carbon): These are defined by the general formula H B C A F J (where 1 < A < 6 and B + J = 2xA + 2). HFC245 (H3C3F5 pentafluoropropane), HFC227 (HC3F7 heptafluoropropane), or HFC365 (H5C4F5 pentafluorobutane) are preferred. These compounds show a very low ozone depletion coefficient and are the most widely used as polyurethane foaming agents worldwide. 2e. HFO (Hydrogen Fluoroolefin): The general formula is H B C A F J (where 1 < A < 6 and B + J = 2xA), that is, a compound containing at least one unsaturated or double bond as well as atoms of fluorine, hydrogen, and carbon. These compounds generally have acceptable values for the ozone depletion coefficient and the global warming potential. HFO1100 (H2C4F6 hexafluorobutene) or HFO1234 (H2C3F4 tetrafluoropropene) are preferred.
[0036] 3. Organic compounds containing carbon, hydrogen, oxygen, and some halogens: These are characterized by the general formula: C A H B X j O D (where x represents a halogen). This group includes some ether derivatives.
[0037] Irreversible blowing agent B2 The term "irreversible blowing agent" refers to a compound or mixture of at least two compounds that increases in volume when heated to a higher temperature from its original temperature, but does not exhibit an equivalent decrease in volume when cooled back to its original temperature. Thus, at least a portion of the volume expansion is permanent and cannot be reversed by cooling back to its original temperature.
[0038] Irreversible blowing agents are preferably based on two mechanisms: first, the decomposition of a compound at high temperature to generate gas, i.e., a chemical reaction rather than a simple change of state of matter. Thus, one preferred irreversible blowing agent B2 is a compound that decomposes when heated to the expansion temperature, releasing gas in the process.
[0039] The second preferred irreversible blowing agent is expandable microspheres. These have a mechanism based on the increase in radius of the solid shell of material caused by the heating and boiling of the hydrocarbon droplets inside. Once the shell is expanded, it cannot be reversed to its previous shape by cooling to its original temperature.
[0040] Preferred blowing agents using the first mechanism are compounds that decompose and release gas when heated. These can be organic or inorganic. Preferred inorganic compounds are sodium borohydride and sodium bicarbonate. Preferred organic compounds are azodicarbonamide, oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide, toluenesulfonylsemicarbazide, and 5-phenyltetrazole. Azodicarbonamide is particularly preferred. To lower the activation temperature, salts, especially zinc oxide, can be added.
[0041] In a preferred embodiment, the irreversible blowing agent B2 has an expansion temperature between 70° C. and 150° C. The expansion or activation temperature is the temperature required to increase the volume of the blowing agent by at least 10 times at 1013 hPa. The volume increase can be caused by the expansion of a gas, the evaporation of a liquid, or the generation of gas by a chemical reaction.
[0042] Foaming Agent Combination The use of both a reversible blowing agent A1 and an irreversible blowing agent B2 is an important feature of the present invention, since only this combination allows the production of a material with the desired sandwich structure.
[0043] The combination of a reversible blowing agent and an irreversible blowing agent is essential to the present invention: in the early moments of mold filling, the reversible blowing agent expands favorably to mold filling, while the irreversible blowing agent expands preferentially in the core of the polymerizable composition while remaining inactive near the surface.
[0044] When the pressure generated by the material during the expansion process reaches a higher level, the reversible components undergo a condensation process in the coolest area (surface) and remain in gaseous form in the core. Thus, the product has a low density in the center, saving material and reducing the overall weight of the product while maintaining a thicker, denser layer on the surface. This dense layer stabilizes the product for everyday use. Without the reversible blowing agent, the polymerizable composition would not be able to completely fill the mold, resulting in a product with a defective shape. Without the irreversible blowing agent, the pressure would be lower and the surface condensation of the complementary reversible blowing agent would be incomplete, resulting in a thin or poor-quality skin.
[0045] The total amount of all blowing agents in the composition is 2 to 8 liters of blowing agent per kg of polymerizable composition, preferably 3 to 6 liters / kg. The "weight of the polymerizable composition" is its total weight as filled into the mold, i.e., it includes components a) to e) and any additional additives that may be present. The volume of blowing agent is given when the blowing agent is fully boiled or expanded at a temperature of 50°C and a pressure of 1013 hPa.
[0046] The research underlying this invention surprisingly showed that products with the desired properties can only be obtained by using a defined ratio of reversible and irreversible blowing agents. Therefore, the proportion of reversible blowing agent based on the total amount of blowing agents is 25% to 75% by volume, with the total amount of irreversible blowing agent remaining at 100% by volume. The volume of the two blowing agents when fully boiled or expanded is calculated as the volume present at a temperature of 50°C and a pressure of 1013 hPa.
[0047] If the proportion of reversible blowing agent is greater than 75% by volume, there is not enough irreversible blowing agent, resulting in excessively poor skin quality. At proportions less than 25% by volume, skin quality is not improved and the mold does not fill properly, resulting in poor geometric accuracy of the part.
[0048] Polyol A1 In the context of this application, the term "polyol component A1" refers to all OH-group-containing organic molecules in the polymerizable composition. Preferably, polyol component A1 has an average OH functionality per molecule of at least 2, more preferably at least 3, and an OH content of at least 15% by weight or an OH value of at least 500 mg KOH / g. The advantage of high OH functionality is a high network density of the resulting polymer matrix, which therefore provides a high glass transition temperature, an important requirement for the desired properties of the resulting solid surface material. Most importantly, high network density improves the abrasion resistance, chemical resistance, hardness, and weathering resistance of these materials.
[0049] Preferred polyols included in polyol component A1 are aliphatic, cycloaliphatic, aromatic, and heterocyclic polyols. When aromatic polyols are present in polyol component A1, they preferably comprise less than 20% by weight, more preferably less than 10% by weight, even more preferably less than 5% by weight, and most preferably less than 1% by weight of polyol component A1. Preferably, the polyols included in polyol component A1 have an OH functionality of at least 2. More preferred polyols in polyol component A1 are selected from the list consisting of glycols, glycerol, propanediol, butanediol, 1,2,10-decanetriol, 1,2,8-octanediol, 1,2,3-trihydroxybenzene, 1,1,1-trimethylolpropane, 1,1,1-trimethylolethane, pentaerythritol, sugars, triethanolamine, and polyethers obtained by reacting the above compounds with ethylene glycol and / or propylene oxide. Amine-initiated polyols based on polyaspartic acid are also preferred.
[0050] The stoichiometric ratio of polyisocyanate component A2 to polyol component A1 was adjusted to 0.85 / 1.0 to 1.2 / 1.0, preferably 0.9 / 1.0 to 1.1 / 1.0, and most preferably 1.05 / 1.0.
[0051] Polyisocyanate component A2 For the purposes of this application, the term "polyisocyanate component A2" refers to all organic molecules in the polymerizable composition that contain at least one isocyanate group. The average isocyanate functionality of all molecules contained in polyisocyanate component A2 is at least 1.8, preferably at least 2.0.
[0052] The term "polyisocyanate," as used herein, is a general term for compounds containing two or more isocyanate groups in the molecule (which will be understood by those skilled in the art to mean free isocyanate groups of the general structure -N=C=O). The simplest and most important representatives of these polyisocyanates are diisocyanates. These have the general structure O=C=NRN=C=O, where R typically represents an aliphatic, cycloaliphatic, and / or aromatic group. Suitable diisocyanates are any diisocyanates obtainable by various methods, for example, by phosgenation in the liquid or gas phase, or by phosgene-free routes, for example, by thermal urethane cleavage. Preferred diisocyanates are those in the molecular weight range of 140 to 400.
[0053] When "polyisocyanate" is generally referred to herein, it refers to monomeric and / or oligomeric polyisocyanates. However, to understand many aspects of the present invention, it is important to distinguish between monomeric diisocyanates and oligomeric polyisocyanates. When "oligomeric polyisocyanates" are referred to herein, they are polyisocyanates formed from at least two monomeric diisocyanate molecules, i.e., compounds that comprise or contain a reaction product formed from at least two monomeric diisocyanate molecules.
[0054] For example, hexamethylene diisocyanate (HDI) is a "monomeric diisocyanate" because it contains two isocyanate groups and is not the reaction product of at least two polyisocyanate molecules:
[0055] [ka] In contrast, a reaction product formed from at least two HDI molecules, yet still having at least two isocyanate groups, is an "oligomeric polyisocyanate" in the context of the present invention. Representative examples of such "oligomeric polyisocyanates" include, for example, monomeric HDI, HDI isocyanurate, and HDI biuret, each of which is formed from three monomeric HDI units:
[0056] [ka]
[0057] (Ideal structural formula) Both monomeric and oligomeric isocyanates are equally useful in the context of the present invention, however, in preferred embodiments of the present invention, the oligomeric polyisocyanate constitutes at least 5 wt. % of the total mass of polyisocyanate component A2, more preferably at least 10 wt. %, even more preferably at least 25 wt. %, and most preferably at least 50 wt. %.
[0058] In a particularly preferred embodiment of the present invention, the oligomeric polyisocyanate constitutes at least 95% by weight, more preferably at least 98% by weight, of the total mass of polyisocyanate component A2. Oligomeric polyisocyanate compositions having a low content of monomeric polyisocyanate can be obtained by reacting monomeric polyisocyanates under suitable reaction conditions, followed by removal of the unreacted monomeric polyisocyanate, for example by thin-film distillation.
[0059] Processes for the preparation of oligomeric polyisocyanates suitable for the present invention are described, for example, in J. Prakt. Chem. 336 (1994) 185-200, DE-A 1670666, DE-A 1954093, DE-A 2414413, DE-A 2452532, DE-A 2641380, DE-A 3700209, DE-A 3900053 and DE-A 3928503 or EP-A 0336205, EP-A 0339396 and EP-A 0798299.
[0060] Particularly suitable for the present invention are 1,4-diisocyanatobutane (BDI), 1,5-diisocyanatopentane (PDI), 1,6-diisocyanatohexane (HDI), 2-methyl-1,5-diisocyanatopentane, 1,5-diisocyanato-2,2-dimethylpentane, 2,2,4- or 2,4,4-trimethyl-1,6-diisocyanatohexane, 1,10-diisocyanatodecane, 1,3- and 1 ,4-Diisocyanatocyclohexane, 1,4-diisocyanato-3,3,5-trimethylcyclohexane, 1,3-diisocyanato-2-methylcyclohexane, 1,3-diisocyanato-4-methylcyclohexane, 1-isocyanato-3,3,5-trimethyl-5-isocyanatomethylcyclohexane (isophorone diisocyanate; IPDI), 1-isocyanato-1-methyl-4(3)-isocyanato Methylcyclohexane, 2,4'- and 4,4'-diisocyanatodicyclohexylmethane (H12MDI), 1,3- and 1,4-bis(isocyanatomethyl)cyclohexane, bis(isocyanatomethyl)norbornane (NBDI), 4,4'-diisocyanato-3,3'-dimethyldicyclohexylmethane, 4,4'-diisocyanato-3,3',5,5'-tetramethyldicyclohexylmethane, 4 ,4'-diisocyanato-1,1'-bi(cyclohexyl), 4,4'-diisocyanato-3,3'-dimethyl-1,1'-bi(cyclohexyl), 4,4'-diisocyanato-2,2',5,5'-tetramethyl-1,1'-bi(cyclohexyl), 1,8-diisocyanato-p-menthane, and 1,3-diisocyanatoadamantane.
[0061] Preferred aromatic polyisocyanates are selected from the list consisting of 1,3-dimethyl-5,7-diisocyanatoadamantane, 1,3- and 1,4-bis(isocyanatomethyl)benzene (xylylene diisocyanate; XDI), 1,3- and 1,4-bis(1-isocyanato-1-methylethyl)benzene (TMXDI) and bis(4-(1-isocyanato-1-methylethyl)phenyl)carbonate, 2,4- and 2,6-diisocyanatotoluene (TDI), 2,4'- and 4,4'-diisocyanatodiphenylmethane (MDI), 1,5-diisocyanatonaphthalene, and combinations thereof.
[0062] The polyisocyanates defined above are equally suitable for use as monomeric polyisocyanates or for the preparation of oligomeric polyisocyanates, which can then be used to prepare the products of the invention.
[0063] Among these polyisocyanates, aliphatic and alicyclic polyisocyanates are particularly preferred. Particularly preferred aliphatic polyisocyanates are selected from the list consisting of 1,6-hexane diisocyanate (HDI), dicyclohexylmethane-4,4'-diisocyanate (H12MDI), isophorone diisocyanate (IPDI), 2,2,4-trimethylhexamethylene diisocyanate (TMDI) and pentamethylene diisocyanate-5 (PDI).
[0064] In a particularly preferred embodiment of the present invention, the aliphatic and cycloaliphatic polyisocyanates as defined above constitute at least 60% by weight of the total mass of polyisocyanate component A2, more preferably at least 80% by weight, even more preferably at least 90% by weight, and most preferably at least 95% by weight. In a very particularly preferred embodiment of the present invention, polyisocyanate component A2, and thus the polymerizable composition, is free of aromatic and araliphatic polyisocyanates.
[0065] Suitable oligomeric polyisocyanates are any polyisocyanates having a uretdione, isocyanurate, allophanate, biuret, iminooxadiazinedione and / or oxadiazinetrione structure, and can be modified from simple aliphatic and / or cycloaliphatic monomeric polyisocyanates, e.g., J. Prakt. Chem. 336 (1994) 185-200, DE-A 1670666, DE-A 19 They can be prepared by modification of the above-mentioned types or from mixtures of at least two such polyisocyanates, as described in DE-A 54093, DE-A 2414413, DE-A 2452532, DE-A 2641380, DE-A 3700209, DE-A 3900053 and DE-A 3928503 or EP-A 0336205, EP-A 0339396 and EP-A 0798299. In the course of their production, the actual modification reaction is generally followed by a further process step to remove unreacted excess monomeric diisocyanate.
[0066] In a further particularly preferred embodiment of the present invention, the oligomeric polyisocyanate constitutes at least 60% by weight of polyisocyanate component A2, more preferably at least 80% by weight, even more preferably at least 90% by weight, and most preferably at least 95% by weight. The use of oligomeric rather than monomeric polyisocyanates contributes to improved safety when handling these materials, since oligomers have lower vapor pressures than monomers.
[0067] According to the invention, combinations of at least two or at least three different monomeric and / or oligomeric polyisocyanates can be used as polyisocyanate component A2.
[0068] It is particularly advantageous to combine at least one monomeric polyisocyanate with at least one oligomeric polyisocyanate to adjust the viscosity of polyisocyanate component A2. The oligomeric polyisocyanate can be based on the monomeric polyisocyanate used. It can also be based on a monomeric polyisocyanate not present as a monomer in polyisocyanate composition A2. The aforementioned combination of oligomeric and monomeric polyisocyanates is also useful for reducing the volume shrinkage during the curing process of the polymerizable composition.
[0069] Catalyst C To accelerate the reaction, conventional catalysts known from polyurethane chemistry can be used. Therefore, the polymerizable composition further comprises a catalyst C. Suitable catalyst C is any compound that mediates the formation of urethane groups from isocyanates and polyols. Such compounds are well known to those skilled in the art, and include, for example, tertiary amines such as triethylamine, pyridine, methylpyridine, benzyldimethylamine, N,N-endoethylenepiperazine, N-methylpiperidine, pentamethyldiethylenetriamine, N,N-dimethylaminocyclohexane, N,N'-dimethylpiperazine, 1,5-diazabicyclo[4.3.0]non-5-ene (DBN), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), or metal salts such as iron(III) chloride, aluminum triethylacetoacetate, zinc chloride, zinc(II) n-octanoate, zinc(II) 2-ethyl-1-hexanoate, zinc(II) 2-ethylcaproate, stearic acid, etc. Zinc(II), zinc(II) naphthenate, zinc(II) acetylacetonate, zinc(II) amidine complexes such as Zn(DBU)2(2-ethylhexanoate)2 or Zn(1-methylimidazole)2(2-ethylhexanoate)2, tin(II) n-octoate, tin(II) 2-ethyl-1-hexanoate, tin(II) ethylcaproate, tin(II) laurate, tin(II) palmitate, dibutyltin(IV) oxide, dibutyltin(IV) dichloride, dibutyltin(IV) diacetate, dibutyltin(IV) dimaleate, dibutyltin(IV) dilaurate, dioctyltin(IV) diacetate, molybdenum glycolate, or combinations thereof.
[0070] Preferred catalysts C are dibutyltin laurate, zinc neodecanoate and bismuth carboxylate.
[0071] Further preferred catalysts are selected from the group consisting of zinc neodecanoate, bismuth carboxylate, ammonium formate, ammonium acetate, ammonium octanoate, tin(II) acetate, tin(II) octanoate, tin(II) ethylhexanoate, tin(II) laurate, dibutyltin diacetate, dibutyltin dilaurate, dibutyltin maleate, dimethyltin dineodecanoate, dimethyltin dioleate, dimethyltin laurylmercurate, dioctyltin dineodecanoate, dioctyltin diacetate, bismuth 2-ethylhexanoate, cobalt 2-ethylhexanoate, iron 2-ethylhexanoate, sodium acetate, sodium octanoate, potassium formate, potassium acetate, potassium ethylhexanoate, potassium octanoate and mixtures thereof.
[0072] The polymerizable composition of the present invention preferably comprises a catalyst as defined above in an amount of from 0.01% to 2% by weight in the final composition.
[0073] method In another embodiment, the present invention provides the following a) providing a polymerizable composition comprising: (i) Polyol component A1; (ii) a polyisocyanate component A2 containing at least 60% by weight of aliphatic and cycloaliphatic polyisocyanates; (iii) at least one reversible foaming agent B1; (iv) at least one irreversible blowing agent B2, and (v) at least one catalyst C; b) injecting the polymerizable composition into a mold; c) A step of curing the polymerizable composition at a temperature of 30°C to 90°C The present invention relates to a method comprising:
[0074] The term "providing a polymerizable composition" refers to the process of mixing components A1, A2, and C of the polymerizable composition so that they can react with each other to give a polymer. Preferably, components B1 and B2 are also uniformly distributed in the polymerizable composition. This can be achieved by any method known in the art and does not pose any additional difficulties.
[0075] The polymerizable composition is then poured into a mold, which is preferably closed and has only a small opening as a pressure outlet, so that the required pressure can be reached at the temperatures defined in this application. Since the polymerizable composition expands during the subsequent curing step due to the activity of the blowing agents B1 and B2, it is preferred to only partially fill the mold. It is particularly preferred to fill 50 to 85% of the mold volume.
[0076] In a preferred embodiment of the invention, the mold is shaped to give a product having a thickness, measured along a surface normal, of 8 to 50 mm, preferably 8 to 40 mm, most preferably 10 to 30 mm, in at least one area, wherein said area is at least 20 mm x 20 mm.
[0077] It is preferred to keep the temperature of the polymerizable composition during process step b) in the range of 0°C to 60°C, preferably 10°C to 50°C.
[0078] Curing in process step c) preferably begins without exposing the polymerizable composition to heat from an external source. Typically, a catalyst present in the composition mediates the formation of urethane bonds. The reaction generated by this process increases the temperature of the polymerizable composition, thus accelerating the reaction.
[0079] The core is the highest temperature because the heat of reaction cannot dissipate. The heat decreases as one approaches the mold wall, i.e., the forming surface of the product, because the wall absorbs some of the heat and thus cools the outer layer of the cured material. This effect is important when a thick-skinned material is desired, because the reversible blowing agent B1 expands in the core of the material but remains liquid or condensed due to the lower temperature near the wall. Thus, the density of the material is lower in the core of the product and higher at its surface. This effect is even more pronounced when the mold walls are actively cooled. Therefore, in a preferred embodiment of the method of the present invention, the mold walls are cooled to maintain a temperature between 30°C and 80°C, preferably between 40°C and 70°C.
[0080] Method step c) is carried out until the polymerizable composition is completely cured, which is achieved when it has cured to a dimensionally stable point.
[0081] In another embodiment of the method, the pressure in the mold is controlled to achieve the desired skin thickness.
[0082] solid surface products In yet another embodiment, the present invention relates to a polymer obtained or obtainable by the process of the present invention. [Brief explanation of the drawings]
[0083] As the diagram shows: [Figure 1] A cross section of a solid surface material is shown. The average density of Zone A, up to 1.5 mm below the surface, is higher than the average density of Zone B, which begins 2.5 mm below the surface.
[0084] The following examples are intended merely to illustrate the invention and are not intended to limit the scope of the claims in any way. [Example]
[0085] Example Example 1: Free foaming carried out in a laboratory equipped to work in ATEX conditions (EXplosive ATmospheres) or in a well-ventilated area A mixture consisting of 40 g of the Component A formulation described in Table 1 below was prepared at room temperature. The components were water-free. The reversible blowing agent was added under manual stirring in a well-ventilated environment. This was stirred manually for 30 seconds and gas entrapment was observed. A proportional amount of Desmodur NZ200®, an oligomeric polyisocyanate with an NCO content of 21% by weight based on aliphatic (hexamethylene diisocyanate) and cycloaliphatic (isophorone diisocyanate) isocyanates, was added at 40°C. The mixture was stirred vigorously, poured into an open paper cup, and free foaming was observed.
[0086] Table 1: Compositions used for free foaming [Table 1] NT (not tested)
[0087] The results show that the uptake of the test samples (reversible foaming agents) under energetic shaking was good in all cases.
[0088] Foaming in the free-foaming container resulted in a volume increase of 2-3 times the initial volume in the three cases tested (1, 3, 4).
[0089] The domes formed had smooth surfaces except for CH2Cl2.
[0090] Example 2: Evaluation of sandwich structure in a molded form (machine pilot plant test) The goal of this innovation is to achieve a sandwich structure with a thick, dense skin and a low-density core in a single operation. To verify the effectiveness of these innovations, this test evaluated core densities with different amounts of foaming agent. Lower core densities result in a greater buildup of material on the outer wall of the piece, creating a thicker skin. The products tested are listed in Table 2 below. The order of addition is the same as in the table.
[0091] Table 2: Ingredients used in the pilot study [Table 2]
[0092] The pre-heated and homogenized formulation components were mixed in a polyurethane injection machine. The materials were poured simultaneously and continuously into an aluminum mold heated to 45°C. When the pouring was complete, the mold was closed. After a few minutes, the mold was opened, and the parts were removed and stored for 24 hours. The parts were trimmed to visualize the cut surface. The extracted sections were evaluated for skin thickness, hardness, and quality.
[0093] Table 3: The following ingredient combinations were tested (amounts in g): [Table 3]
[0094] Formulation A (comparison): Skin density measurement The resin, previously dried without a blowing agent, was reacted with isocyanate. Dense, non-foamed and translucent pieces were obtained. The density of the pieces was measured by immersion. The density was approximately 1100 kg / m3. In the case of sandwich parts with a foamed core, a completely dense skin without microbubbles (as confirmed by microscope) can be assumed to have a similar local density in the skin region.
[0095] Determining Core Density (All Examples) Core density was calculated as follows: All apparent densities were measured by Archimedes' method (immersion) or by weighing and measuring rectangular samples. Pieces were cut and the skin formed on each side was inspected and measured under high magnification with an accuracy of 50 microns. If homogeneous and bubble-free, the density was 1100 kg / m 3 If not, a lower density was assumed.
[0096] Knowing the thickness and density of the skin, the weight of the skin was calculated. By mathematical calculation (subtracting the skin weight from the total weight and the skin volume from the total weight), the core density was calculated. This method was tested in a specific case by mechanically removing the skin and measuring the density of the foam core separately. The correlation was found to be correct.
[0097] result Table 4: Compositions 1 and 3 containing only one type of blowing agent (comparison) [Table 4]
[0098] The absence of an irreversible blowing agent in composition 1 prevents the formation of a dense skin. The absence of a reversible blowing agent in composition 3 made it difficult to fill the mold, even using a special mold having a thickness of only 20 mm.
[0099] Table 5: Composition 2 (comparison) [Table 5]
[0100] Low concentrations of irreversible blowing agent produced a skin that was not dense and was slightly foamed.
[0101] Table 6: Results for Composition 4 (Invention) [Table 6]
[0102] In this series of tests, a complete and relatively thick skin was observed, regardless of density. The core density was proportional to the total density, and in all cases there was an excellent gradient between core and skin density, indicating an optimal sandwich structure.
[0103] Table 7: Results for Composition 5 [Table 7]
[0104] In this series of tests, the ratio between the two blowing agents was increased. This composition still gave an excellent skin, but the core density was higher, resulting in slightly less efficient distribution of the material.
[0105] A comparison of Composition 2 on the one hand with Compositions 4 and 5 on the other hand shows that simply combining a reversible and an irreversible blowing agent is not sufficient to produce a sandwich material with completely satisfactory properties. The concentration of the irreversible blowing agent, as well as the ratio of the two blowing agents, must be optimized. However, for many applications, a slightly foamed surface, such as that obtained with Composition 2, is sufficient. This point is further analyzed in Example 4.
[0106] Example 3: Mechanical testing of different thicknesses and geometries To evaluate the performance of the material at different thicknesses, three pieces were made using a stepped mold. The formulation used was Example 2, No. 4. It was filled into stepped molds with thicknesses of 6 mm, 12 mm, 22 mm, and 32 mm and a total volume of 6.0 liters.
[0107] To facilitate material flow and filling, the mold was tilted 15 degrees, with the thickest part located at the top. The average working temperature of each component was 45°C. The mold was maintained at the same temperature. The materials were mixed in a small pilot continuous batch mixer. The casting time was 22.5 seconds. A larger machine with a greater output should avoid this issue. In any case, tests performed indicate that the mechanical properties and functionality of the pieces were not affected.
[0108] Table 8: Results using different product thicknesses [Table 8]
[0109] The density distribution and skin thickness characteristics were fairly stable with thickness. While the total density of the part varied significantly with thickness, the separate densities of the skin and foam were much more stable. For parts with thicknesses between 10 mm and 30 mm, skin thicknesses of 1.7 mm to 2.2 mm were obtained. The skin density was approximately 1,100 kg / m 3 It was.
[0110] The sandwich structure was not obtained for products less than 6 mm thick. The weight and overall or apparent density of the part varied with thickness, but the local density of the surface and core, as well as the general properties of the material, were maintained. It is entirely feasible to produce pieces with thicknesses between 6 mm and 30 mm from the same piece. This piece has the desired sandwich structure with a thick, hard skin and a foam core in all areas with a local thickness of 10 to 30 mm, and no visible defects are observed.
[0111] Example 4: Sandwich Structure Evaluation in Molded Foam (Controlled Laboratory Conditions) In parallel with Example 2, a test with the same objectives was conducted under laboratory conditions and with manual stirring to allow for very precise control of the parameters. To verify the effectiveness of these innovations, the test evaluated the production of materials while maintaining the same total amount of blowing agent in all samples. Only the ratios of the two blowing agents were varied. The products produced were as follows. The order of addition was the same as in the table.
[0112] Table 9: Ingredients used in the pilot study [Table 9]
[0113] The tempered components were mixed by hand. The mixture was then poured into a closed aluminum mold tempered at 45°C. The mold was immediately closed. After a few minutes, the mold was opened, and the part was removed and stored for 24 hours. The part was then trimmed to reveal the internal structure. The extracted part was measured for skin thickness, hardness, and visual quality assessment.
[0114] Shape accuracy was determined by measuring the actual density of the product by water immersion and comparing the measured density with the theoretical density of a part that completely fills the entire volume of the mold.
[0115] Table 10: Formulations tested in this example: (amounts in parts by weight) [Table 10]
[0116] Each blowing agent has a different density when expanded, and is given here in liter quantities (total quantity in liters) taking into account normal conditions of pressure and temperature.
[0117] Test volume (liters) [Table 11]
[0118] For the reversible blowing agent, the perfect gas equation was used: PV = nrT, where n = m / Mw, P = 1 Atm, r = 0.082, T = 298°K, and Mw is 149.6 g / mol in this example according to the manufacturer's instructions. m is the mass of the reversible blowing agent in grams of the formulation. For the irreversible blowing agent, the density of the material after expansion given by the manufacturer, in this case 12 g / l, was used.
[0119] Although normal conditions of pressure and temperature are used in this embodiment, for greater consistency in the claim language, the volumes are fixed at a temperature of 70° C. In each case, Charles' gas law VT=k was used to convert volumes to other temperatures.
[0120] Table 11: Results [Table 12]
[0121] The optimum relationship between the two blowing agents is achieved when they are balanced in volume (not weight). The best example is given by the formula LAB3.
[0122] The results show that a minimum amount of irreversible blowing agent of 25% by volume, based on the total volume of the two blowing agents, is required to obtain at least satisfactory skin quality. Further increasing the irreversible blowing agent proportion to 75% by volume (LAB4) further improves surface quality. Beyond that, no improvement can be achieved. However, increasing the proportion of irreversible blowing agent also leads to an undesirable effect: a decrease in the geometric accuracy of the molded part. Therefore, when the proportion of irreversible blowing agent exceeds 75% by volume, the decrease in geometric accuracy and the improvement in surface quality are no longer balanced, and therefore this content of irreversible blowing agent is the most useful amount.
[0123] The reduction in shape accuracy reflects the difficulty of filling the mold completely and uniformly. In industrial conditions where large, complex molds are used, these filling difficulties cause local defects in the product.
Claims
1. A polyurethane component having at least one area measuring at least 20 mm x 20 mm, (i) Thickness of 8 mm to 50 mm, (ii) 0.9 g / cm³ measured within 1.5 mm below the surface along the surface normal. 3 ~1.4 g / cm 3 The average density, and (iii) In the portion of the polymer at least 2.5 mm below the surface, measured along the surface normal, 0.25 g / cm³ 3 ~0.8 g / cm 3 Characterized by the average density, a) Polyol component A1; b) Polyisocyanate component A2 comprising at least 60% by weight of aliphatic and alicyclic polyisocyanates; c) At least one reversible blowing agent B1 that changes from liquid to gas phase when exposed to a determined temperature and pressure, but returns to the liquid phase when the pressure increases or the temperature decreases; d) At least one irreversible blowing agent B2 that increases in volume when heated from its original temperature to a higher temperature, but does not exhibit an equivalent decrease in volume when cooled back to its original temperature, and e) Obtained or can be obtained by polymerizing a composition containing at least one catalyst C, Herein, the volume of the reversible blowing agent is 25% to 75% by volume, and when the volume of the irreversible blowing agent is added, the total is 100% by volume, and the volume of the blowing agent is given based on a temperature of 50°C and a pressure of 1013 hPa, the polyurethane component.
2. The polyurethane component according to claim 1, wherein the total amount of foaming agent present in the polymerizable composition is 2 to 8 liters of foaming agent per 1 kg of polymerizable composition, and the volume of foaming agent is given as described in claim 1.
3. The polyurethane component composition according to claim 1, wherein the reversible blowing agent B1 has a boiling point of 5°C to 50°C at atmospheric pressure.
4. The polyurethane component according to claim 1, wherein expandable microspheres are used as an irreversible foaming agent.
5. The polyurethane component according to claim 1, wherein the irreversible foaming agent B2 has an expansion temperature of 70°C to 150°C.
6. The polyurethane component according to claim 1, wherein the polyol component A1 has an average OH functional value of at least 2 per molecule and an OH content of at least 15% by weight.
7. The polyurethane component according to claim 6, wherein the polyol component A1 comprises at least one compound selected from the list consisting of glycol, glycerol, propanediol, butanediol, 1,2,10-decanetriol, 1,2,8-octantriol, 1,2,3-trihydroxybenzene, 1,1,1-trimethylolpropane, 1,1,1-trimethylolethane, pentaerythritol, sugars, and polyethers obtained by reacting the aforementioned compounds with ethylene glycol and / or propylene oxide.
8. The polyurethane component according to any one of claims 1 to 7, wherein the component is selected from the group consisting of bathroom components, kitchen fixtures, shells for electrical and electronic devices, cases for electrical equipment, vehicle components, building components, indoor furniture and outdoor furniture.
9. a) A step of providing a polymerizable composition comprising the following (i) Polyol component A1; (ii) Polyisocyanate component A2 comprising at least 60% by weight of aliphatic and alicyclic polyisocyanates; (iii) At least one reversible blowing agent B1 that changes from liquid to gas phase when exposed to a determined temperature and pressure, but returns to the liquid phase when the pressure increases or the temperature decreases; (iv) at least one irreversible blowing agent B2 that increases in volume when heated from its original temperature to a higher temperature, but does not exhibit an equivalent decrease in volume when cooled back to its original temperature, and (v) at least one catalyst C; Here, the volume of the reversible blowing agent is between 25% and 75% by volume, and when the volume of the irreversible blowing agent is added, the total becomes 100% by volume, and the volume of the blowing agent is given based on a temperature of 50°C and a pressure of 1013 hPa. b) The process of injecting the polymerizable composition into a mold; c) A method comprising the step of curing a polymerizable composition at a temperature of 30°C to 90°C.